Liver histology of Wistar rats (Rattus norvegicus) following oral administration of 50% ethanol - Liah Kodariah; Rahmad Rezaldy; Suryanata Kesuma; Farhan Baehaki (Journal of Sustainability Science and Technology, 2022)
Ethanol, also known as ethyl alcohol, pure alcohol, and alcohol, is a toxic, volatile, flammable, and colourless liquid. Alcohol is the most commonly consumed alcoholic beverage in everyday life. EtOH is a common abbreviation for ethanol, where "Et" stands for the ethyl group (C2H5). Sugar fermentation to ethanol is one of the earliest organic reactions ever performed by humans; ethanol consumption has also been known for a very long time. This study aims to determine the histology of the liver in Wistar rats (Rattus norvegicus) by orally administering ethanol at a concentration of 50 percent. The method used in this study was an experimental study by looking at the histology of rat liver. Rats were divided into two groups, with seven rats each. Group 1 was given 50% ethanol orally for seven days, and group 2, as a control, was only given orally with distilled water. After seven days, the rats were slaughtered, and their livers were extracted for further histological preparations. In the histology results of group 1, the histological images of the livers of the rats P1, P2, P3, P4, P5, P6 and P7 were abnormal or damaged. In the presence of necrotic cells, oral administration of 50 percent alcohol causes damage to hepatocyte cells, as determined by the study's findings. However, in general, hepatocyte cell damage in the liver produces a score of 1.7, which indicates a change leading to cell damage.